Художник Ян Мирослав Пескe (1870–1949) – мистець пограниччя культур - Поляновська, Й. (Студії мистецтвознавчі, 2008)
Musée d’Art Morderne de Collioure (until recently the Musée de Collioure Fonds Peské) was founded in Collioure (Lanquedoc) by the Polish painter Jan Mirosław Peské who had arrived in Collioure from the Ukraine. Born on July 27, 1870 at Golta in the former Cherson province, Peské naturalized in France in 1921 and died on March 21, 1949 in Le Mans. He studied in Kiev, Odessa, Warsaw and from 1890 also in Paris, where he joined the Post-Impressionist avant-garde in 1894.